THE EFFECT OF ORAL MOTOR EXERCISE AND SEMANTIC DIVERGENCE ON IMPROVING SPEAKING ABILITY OF STROKE PATIENTS - Hendri Heriyanto; Deta faizah; Husni (Proceeding of Banten Internasional Conference on Health Advancement and Research, 2026)
Non-communicable diseases have shown a changing trend, marked by a continuous increase in morbidity and mortality rates, with stroke being one of the leading causes. Among stroke patients, approximately 21% to 38% experience aphasia, a disorder that affects communication skills, particularly in understanding and expressing language. Effective rehabilitation is crucial to restoring these functions. Two non-pharmacological interventions, Oral Motor Exercise and Semantic Divergent Therapy, have been recognized for their potential to enhance speech ability in stroke survivors. This study aimed to determine the effect of combining Oral Motor Exercise and Semantic Divergent Therapy on improving speech ability in stroke patients. A quasi-experimental design with a pretest-posttest control group approach was used, involving 40 participants selected through purposive sampling. The intervention group received both therapies, while the control group underwent AIUEO therapy. Results showed that the mean speech score of the intervention group increased from 15.40 to 20.85, while the control group's score rose from 15.30 to 19.45. The Independent T-test analysis revealed a p-value of 0.000 (p < 0.05), indicating a significant difference between groups. These findings demonstrate that Oral Motor Exercise combined with Semantic Divergent Therapy effectively enhances speech ability in stroke patients. Therefore, this combined approach is recommended as an effective non-pharmacological rehabilitation intervention to support recovery and improve communication functions after stroke.